The Effect of Social Media Marketing and E-WOM on Purchase Intention of TikTok Users - Saputra, Riski Riadi; Darpito, Surpiko Hapsoro; Oetomo, Hadi; Sutanto, Hery (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to analyze the role of E-trust as a mediating variable on the influence of social media marketing and e-WOM on purchase intention of TikTok users in Sleman Regency. The sampling technique uses a non-probability sampling technique with purposive sampling. Data obtained using a questionnaire technique in the form of a Google form, distributed online to 100 respondents. The data analysis method in this study used the Structural Equation Modeling-Partial Least Square (SEM-PLS) method with the SmartPLS 4.0 data processing program. The results of this study indicate that social media marketing has a positive and significant influence on purchase intention, e-WOM has a positive and significant influence on purchase intention, social media marketing has a positive and significant influence on E-trust, e-WOM has a positive and significant influence on E-trust, E-trust has a positive and significant effect on purchase intention, social media marketing has a positive and significant effect on purchase intention through E-trust as a mediating variable, e-WOM has a positive and significant influence on purchase intention through E-trust as mediating variable.